Clinical characteristics and outcomes of chronic nonbacterial osteomyelitis in children: a multicenter case series - Le Ma; Haimei Liu; Hanyun Tang; Zhiyong Zhang; Lixia Zou; Haiguo Yu; Li Sun; Xiaozhong Li; Xuemei Tang; Meiping Lu (BMC, 2022)
Abstract Objective The aim of this study was to evaluate demographic, clinical, laboratory, imaging, histopathology characteristics, and treatment responses of children with Chronic nonbacterial osteomyelitis (CNO). Methods Retrospective multi-center case series study of pediatric patients diagnosed with CNO treated at five tertiary centers in south China. Results Totally there were 18 patients diagnosed as CNO between 2014 and 2020. The median age of onset was 9.2 years (range 3.7-13.1) and 55.6% were female. Median delay in diagnosis was 10.9 months (range 1.0-72.0). The most frequent presenting symptoms were bone pain (100%) and fever (44.4%). Most patients had more than one lesion (median of 5, range 1-7). Most frequently affected bones were tibiofibula (88.9%) and femur (77.8%). The MRI characteristics mainly presented as bone edema and hyperintensity in bone marrow. Bone biopsy was conducted in 11 patients (61.1%) with inflammatory cells infiltration manifested as chronic osteomyelitis, and none showed bacterial infection or tumor. In treatment, non-steroid anti-inflamatory drugs (NSAIDs) is used as the first-line drug followed by steriods, methotexate (MTX), salazosulfadimidine (SASP), Bisphosphonates and TNF-α inhibitor. Two refractory cases received combination therapy with Bisphosphonates and TNF-α inhibitor, and achieved good therapeutic effect. Conclusions The present study described a multicenter series of CNO from south China and highlighted the clinical features, laboratory tests, imaging characteristics and treatment outcomes. Increasing awareness of this disease is important to decrease time to diagnosis, improve access to treatment, and reduce complications.